The Future of Mobility - Brownell, Peter; Light, Thomas; Sorensen, Paul; Samaras, Constantine; Kalra, Nidhi (RAND Corporation, 2023)
What might one expect for the future of mobility in the United States in 2030? Mobility is defined as the ability to travel from one location to another, regardless of mode or purpose. RAND researchers used a six-step scenario development process to develop two thought-provoking scenarios that address this question. The six steps are (1) select influencing areas (domains that affect mobility directly; here, demographics, economics, energy, transportation funding and supply, and technology); (2) elicit projections on descriptors (via expert workshops); (3) integrate into scenario frameworks (using two analysis methods and a computer-based tool); (4) produce scenario narratives (based on the clusters produced by the tool); (5) draw consequences for future mobility (by estimating future growth in travel modes based on the projections); and (6) create wild-card scenarios (by looking at events that might disrupt trends). Three key drivers differentiate the resulting scenarios: the price of oil, the development of environmental regulation, and the amount of highway revenues and expenditures. In scenario 1, No Free Lunch, oil prices for consumers and business increase because of greenhouse gas–reduction legislation, and states and localities implement road pricing, which results in higher revenues. Mobility in this scenario is lower because of the higher costs of driving. Scenario 2, Fueled and Freewheeling, assumes that oil prices remain steady, no major environmental legislation is passed, and highway revenues decline, which results in generally higher mobility, especially miles driven. By making potential long-term mobility futures more vivid, the authors' aim is to help planners and policymakers at different levels of government and in the private sector better anticipate and prepare for change and, in the process, make better decisions now to affect the future of mobility in the United States.